Rancang Bangun Smart Trash Can Dengan NodeMCU ESP8266 Menggunakan Sistem Monitoring Berbasis Komunikasi Telegram Messenger - Laily Muntasiroh; Radiktyo Nindyo Sumarno (Universitas Nusa Putra, 2022)
Smart Trash Can or smart trash can uses sensors and servo motor actuators. The sensor used is the ultrasonic sensor HC-SR04. Sensor 1 is used to detect the presence of people, sensor 2 is used to detect the height of the volume of the trash can, and the servo motor is used to open and close the trash automatically. This Smart Trash Can is equipped with a battery powered by solar cells. So that the trash cans that are inside and outside the room will still be able to communicate via IoT which in this study uses a complete device / laptop with the Telegram Messenger application as the monitoring system.